2019
DOI: 10.1002/ima.22312
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided diagnosis of brain abnormalities using texture analysis of MRI images

Abstract: The drive of this study is to develop a robust system. A method to classify brain magnetic resonance imaging (MRI) image into brain‐related disease groups and tumor types has been proposed. The proposed method employed Gabor texture, statistical features, and support vector machine. Brain MRI images have been classified into normal, cerebrovascular, degenerative, inflammatory, and neoplastic. The proposed system has been trained on a complete dataset of Brain Atlas‐Harvard Medical School. Further, to achieve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Texture analysis is an emerging computer-aided diagnosis technology that can quantitatively display subtle changes in image pixels and arrangement, independence of image grayscale and subjective factors of the diagnostics, and its evaluation value for various tumor heterogeneities is obtained. It has generally been confirmed that it has gradually become a research hotspot in recent years (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 95%
“…Texture analysis is an emerging computer-aided diagnosis technology that can quantitatively display subtle changes in image pixels and arrangement, independence of image grayscale and subjective factors of the diagnostics, and its evaluation value for various tumor heterogeneities is obtained. It has generally been confirmed that it has gradually become a research hotspot in recent years (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 95%
“…Classical machine-learning algorithms have been used for brain tumor grading and other automated medical image analysis tasks. [25][26][27] The limitation of these techniques is the need to handcraft suitable features from the images/volumes, which are then fed to the classifier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A modified segmentation algorithm have been implied with the use of GLCM and minimal LBP(local binary pattern).Here classification have been performed by NB-PKC that precisely determines the position thereby decreased the human errors. [6] The suggested technique implemented statistical features, SVM and Gabor texture. The MRI images was classified into degenerative, inflammatory, cerebrovascular, normal and and neoplastic.…”
Section: Related Workmentioning
confidence: 99%